2014
DOI: 10.1002/cbic.201402193
|View full text |Cite
|
Sign up to set email alerts
|

Bioorthogonal Fluorescent Labeling of Functional G‐Protein‐Coupled Receptors

Abstract: Novel methods are required for site-specific, quantitative fluorescence labeling of G protein-coupled receptors (GPCRs) and other difficult-to-express membrane proteins. Ideally, fluorescent probes should perturb native structure and function as little as possible. We evaluated bioorthogonal reactions to label genetically encoded p-acetyl-l-phenylalanine (AcF) or p-azido-l-phenylalanine (azF) residues in receptors heterologously expressed in mammalian cells. We found that keto-selective reagents were not truly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 89 publications
(88 reference statements)
2
51
0
Order By: Relevance
“…Various bicelle systems have been shown to retain the structural and functional integrity of membrane proteins (18). Previously, we have shown that the binding product between 11CR and photobleached Alexa488-labeled Rho in the bicelle system could be repeatedly photoactivated, demonstrating the regeneration of mature pigment (19). In our study, we used Trp fluorescence to show that the photobleached Rho in bicelles bind with 11CR or 9CR with comparable kinetic rate constants.…”
Section: Discussionmentioning
confidence: 65%
“…Various bicelle systems have been shown to retain the structural and functional integrity of membrane proteins (18). Previously, we have shown that the binding product between 11CR and photobleached Alexa488-labeled Rho in the bicelle system could be repeatedly photoactivated, demonstrating the regeneration of mature pigment (19). In our study, we used Trp fluorescence to show that the photobleached Rho in bicelles bind with 11CR or 9CR with comparable kinetic rate constants.…”
Section: Discussionmentioning
confidence: 65%
“…S3). The azidoF-containing receptor was assembled as a monomer into lipid discs (10) and then labeled with the fluorescence acceptor (Alexa Fluor 488) using the strain-promoted alkyne-azide cycloaddition reaction (21,22). Approximately 90% of labeling was achieved under these conditions, whereas no labeling was observed with the unmodified receptor (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Temperatures were controlled with a VWR water bath and constantly monitored using an Omega Thermister to within 0.5°C of the desired temperature. Retinal binding was observed by quenching of intrinsic tryptophan fluorescence measured as a decrease in emission at 330 nm, essentially the inverse of the retinal release assay (21,22,26,29,30). To minimize rhodopsin bleaching, excitation was tempered by a neutral density (optical density 1.7) filter and emission bandwidth was expanded to 20 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Essentially, this process entails running a retinal release experiment in reverse (26) where instead of observing the relief of quenching of intrinsic tryptophan fluorescence by retinal exit one now monitors the decrease of tryptophan fluorescence emission caused by the tryptophan residues undergoing FRET to the newly bound retinal (21,22,(27)(28)(29)(30)(31). In contrast to traditional absorbance-based assays, this approach allows for the detection of any chromophore in the binding pocket and not just those retinals that have formed a protonated Schiff base, thus enabling the study of both 11CR and ATR binding (the latter of which is "spectroscopically silent" in traditional absorbance binding assays).…”
Section: Use Of Fluorescence To Measurementioning
confidence: 99%
See 1 more Smart Citation